That Eminent Tribunal : Judicial Supremacy and the Constitution - Wolfe, Christopher (Book collections on Project MUSE., 2004)
The role of the United States Supreme Court has been deeply controversial throughout American history. Should the Court undertake the task of guarding a wide variety of controversial and often unenumerated rights? Or should it confine itself to enforcing specific constitutional provisions, leaving other issues (even those of rights) to the democratic process?